2012
DOI: 10.1016/j.jpeds.2011.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Transfusions on Abdominal Sonographic Abnormalities in Children with Sickle Cell Anemia

Abstract: Objective To assess the effects of chronic erythrocyte transfusions on prevalence of sonographic incidence of organ damage in children with sickle cell anemia (SCA). Study design Children (n=148; mean age, 13.0 years) with SCA, receiving chronic transfusions (average, 7 years) underwent abdominal sonography at 25 institutions. After central imaging review, spleen, liver and kidney measurements were compared with published normal values. Potential relations between ultrasound, clinical and laboratory data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
4
11
3
Order By: Relevance
“…In our study, 70% of the patients treated with chronic transfusions had sonographically visible spleens without autosplenectomy, similar to a prior study reporting a rate of almost 80% 15 . We found that patients who were treated with chronic transfusions were more likely to have intrasplenic nodules, and all patients treated with chronic transfusions had echogenic spleens on sonography.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, 70% of the patients treated with chronic transfusions had sonographically visible spleens without autosplenectomy, similar to a prior study reporting a rate of almost 80% 15 . We found that patients who were treated with chronic transfusions were more likely to have intrasplenic nodules, and all patients treated with chronic transfusions had echogenic spleens on sonography.…”
Section: Discussionsupporting
confidence: 89%
“…Hydroxyurea decreases the frequency of functional asplenia among patients with SCD and has been associated with splenomegaly without sequestration 13 , 14 . Long‐term transfusion therapy has not been effectively shown to prevent splenic dysfunction, but in a study of 148 patients age 5 to 19 years with HbSS treated with chronic transfusions, only 20% had surgical splenectomy or autosplenectomy, and more than 33% had splenomegaly 15 . Transfusion therapy can lead to iron overload, which causes the spleen to be hypointense on T2‐weighted magnetic resonance imaging (MRI) 16 .…”
mentioning
confidence: 99%
“…With such a high percentage of emergent patients receiving transfusions or hydroxyurea, it warrants further prospective study to determine if these patients are at higher risk of hepatobiliary complications irrespective of therapy or if some therapies, as seen in SWiTCH, may accelerate hepatobiliary complications. The higher number of patients on chronic transfusion confirm SWiTCH data that identified that two thirds of patients on chronic transfusion for a mean of 7 years had hepatobiliary disease …”
Section: Discussionsupporting
confidence: 71%
“…18,19 In our study gall stones were detected in (14%), which is lower than some studies like Gumiero et al in which gall stones were detected in 45% but similar to studies like Mc Carville et al and Bokade in which gall stones were found in 21% and 29% respectively. 20,21 In our study, there were 10 % of patients who had gall bladder sludge, which is similar to studies by Mahebba (12 %) and Dalia (14 %).…”
Section: Discussionsupporting
confidence: 90%